Direct carotid puncture for endovascular thrombectomy in acute ischemic stroke. (6th April 2019) - Roche, Adam; Griffin, Emma; Looby, Seamus; Brennan, Paul; O'Hare, Alan; Thornton, John; Boyle, Karl; Williams, David; Moynihan, Barry; Power, Sarah
Abstract : Background: Mechanical thrombectomy is the standard of care for acute ischemic strokes with proximal intracranial occlusion. Arterial access is commonly achieved with femoral artery puncture, although this is not always possible. In this case series, we describe 11 cases of anterior circulation stroke where direct carotid puncture was used to obtain vascular access. Methods and materials: A review of a prospectively maintained thrombectomy database over a 2-year period (August 2016 – August 2018) was undertaken to identify cases where direct carotid access was performed. CT and angiographic imaging were reviewed. Indications for carotid access, techniques used, technical success of procedure, recanalization rates, procedure-related complications, and patient outcomes were assessed. Results: Eleven patients out of 498 overall thrombectomy procedures (2.2% thrombectomies) underwent direct carotid access. Median National Institutes of Health Stroke Scale was 20. Seventy three percent of patients received intravenous thrombolysis. The direct carotid approach was performed following the failed femoral approach due to unfavorable aortic arch anatomy, vessel tortuosity, and severe atherosclerotic disease. Direct carotid puncture was successful in 10 patients, and unsuccessful in one. Successful recanalization (TICI 2b–3) was achieved in eight patients. One patient had spontaneously recanalized on angiography. There was failed recanalization in one patient with tandem ICA and M1 occlusion. Carotid access complications included one patient with both neck hematoma and asymptomatic ICA dissection, and one of delayed central retinal artery occlusion. Conclusion: This case series highlights direct carotid puncture as a successful alternative when the femoral approach is not possible, allowing thrombectomy in patients who would otherwise be unsuitable.